Effect of the game time schedule under the physical performance of professional soccer players - dos Santos, R. R. C.; Almeida, G.; Asano, R. Y.; Rodrigues, R. R.; da Silva, M. O.; dos Santos, P. R. C. (International Journal of Sports Science, 2018)
The physical performance of soccer players is multifactorial, among these, the game schedule seems to be a factor to be considered, after all, the time of the day in which the match is played, either daylight or nightfall, can influence directly on their performance. Therefore, this study aimed to investigate the influence of game time has on the physical performance of professional soccer players in relation to distance traveled and intensity of effort during game play. In order to do so, 24 professional players from a team of the 4th division of Brazilian soccer were evaluated, in which the observed matches (referenced as n = 13 in the spreadsheet) were performed in the afternoon (4:00 PM, referenced as n = 8 in the spreadsheet) and in the evening (9:00 PM referenced as n = 5 in the spreadsheet). All the players, except the goalkeeper, were equipped during matches with the Global Positioning System, and through the QSports software® were obtained the values of distance traveled and intensity relative to the distance traveled in the game, which is divided into three levels: 0 - 10 km/h (Low), 11 - 18 km/h (Average), and 19 - 26 km/h (High). Thus, the findings did not present any differences in relation to the distance traveled; however, in the matches held at 9:00 PM, the players ran a greater distance in average intensity than those at 4:00 PM. In conclusion, it is suggested that games performed after 9:00 PM influence the intensity in which the match is played, being covered greater distance in average intensity.